THE POLYPHONIC VOID: NARRATIVE MULTIPLICITY AND THE SUBVERSION OF AUTHORIAL DOMINANCE IN FAULKNER’S “AS I LAY DYING” - Jumaeva Nilufar Gulomovna, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract. This article investigates the architectural complexity of William Faulkner’s modernist masterpiece, “As I Lay Dying”, through the lens of Mikhail Bakhtin’s theory of polyphony. By deconstructing the novel’s 59 monologues delivered by 15 discrete narrators, this study explores how Faulkner achieves a radical subversion of authorial dominance, replacing a singular, omniscient “truth” with a fragmented network of subjective realities. The analysis focuses on the interplay between multiplicity of narrative voices and the technical execution of stream of consciousness, arguing that these methods serve to expose the epistemological limitations of human perception. Central to this inquiry is the role of Addie Bundren, whose posthumous monologue creates a central void that both anchors and destabilizes the surrounding narratives. By examining the linguistic variation across characters—from Cash’s mechanical precision to Darl’s poetic clairvoyance—the study demonstrates how Faulkner’s polyphonic structure mirrors the internal isolation and the breakdown of communal truth within the Bundren family. Ultimately, this research posits that the novel’s formal innovation is not merely a stylistic choice but a thematic necessity, illustrating the profound incommunicability of grief and the inherent fragmentation of the modern human condition.